Preparing for completely smoke-free mental health settings: findings on patient smoking, resources spent facilitating smoking breaks, and the role of smoking in reported incidents from a large mental health trust in England - Sohal, Harpreet; Huddlestone, Lisa; Ratschen, Elena (MDPI, 2016)
Introduction: Despite high smoking prevalence and excessive smoking-related morbidity and mortality among people with mental disorder compared to the general population, smoking treatment is often neglected in mental health settings. The UK National Institute of Health and Clinical Excellence (NICE) recently issued public health guidance stipulating completely smoke-free mental health settings. This project evaluated existing smoking-related practices in preparation for guidance implementation. The objectives were to: audit the recording of smoking-related information and treatment provision; explore current arrangements relating to the facilitation of patient smoking; measure staff time spent and identify costs of facilitating smoking; and explore the role of smoking in smoking-related incidents.